The influence of work environment and digitalization of accounting on career interest in public accountants: financial rewards as a moderating variable - Safier Ramdani; Asep Sutarman (SEAN Institute, 2024)
The aim of this study is to determine the impact of career interest in the Public Accounting Office (PAC) on the working environment variable and the digitalization of accounting in moderation by the financial reward variable in accounting students in generation Z. The method used is descriptive-quantitative, with a population sample of as many as 309 LLDIKTI Region III accounting student. The work environment has significant negative influences and financial appreciation has significant positive influences on career interests, but the positive influence of digital accounting is not significant. This is because the digitization of accounting, especially artificial intelligence, is still controlled by humans so it does not cause too much concern about losing his career.